EMU-Synchronization Enhanced Mobile Underwater Networks for Assisting Time Synchronization Scheme in Sensors (International Journal of Engineering and Computer Science, 2017)
Efficient data transmission is a critical issue for wireless sensor networks (WSNs). Clustering is an effective and practical way to enhance the system performance of WSNs. In this paper, we propose a cluster-based synchronization algorithm for underwater acoustic sensor networks based on MU-Sync, called EMU-Sync. In underwater sensor networks the time synchronization is challenging for long propagation delay, sensor node mobility and energy consumption. The improved performance of MU-Sync from the EMU-Sync gives the ability to maintain its low Complexity. This is possible by allowing the cluster head to calculate the skew and the offset from the view of both a cluster head and a neighboring node. Simulation results confirms that EMU-Sync offers better performances than MU-Sync in both accuracy and energy efficiency.